Debates alrededor del ciberfeminismo : cyborg y cibergrrrl-ism - Ortiz Sevilla, Paola Belén (2018)
This article talks about the debates around the cyber feminism from elements like: the body, gender and the sexuality. This context analyzes two visions, the cyborg and cibergrrrl-ism to determinate if those are activist strategies. The execution consist in compare the speeches of different feminism collective and which are the characteristics del cyber feminism on the Latin American Web such us: the Pillku Magazine, the newspaper Mujeres en Red, the Karisma Foundation and the EnRedadas blog. Those pose that are spaces of action and social change from cyber cultural or artistic practices of feminist groups. The analysis contains cybernetic characteristics of the virtual spaces about social constructions around hegemonies and mechanisms of power, inside the historic scheme of the activism that have feminist collectives on the cyberspace. The Methodology used here is this research is the netnography and the discourse analysis web scientific investigation and speech analysis to describe the communicative practices on the virtual spaces chosen and interpreting the phenomena of cyberspace. Communication is looked like the novelty place to talk about public opinion and political action. In this case we show the strategic ideas exposed in creative way to the virtual community. It shows strategic ideas exposed in a creative way on the virtual community. Cyber feminism reflects about the feminist theories and the queer theory, to about subversion and transgression of the hetero-normative. The cyborg has a political connotation around techno science and the cibergrrrl-ism looked like a “new war scream” on the Web.